Diplomasi Maritim Indonesia dalam Perumusan ASEAN Outlook on the Indo-Pacific - Luna Khoirunissa; Maria Indira Aryani (Andalas Institute of International Studies, 2022)
ASEAN Outlook on the Indo-Pacific (AOIP) is an Indo-Pacific cooperation framework established by ASEAN on June 2019. Indonesia was one of the founding fathers of ASEAN—known for its contributions as a inisiator of many cooperations and collaborations in the region—is also known for its great contributions in constructing the AOIP framework. Therefore, this paper aims at explaining about Indonesia’s maritime diplomacy took part in formulating the AOIP through the ASEAN internal forums and the ASEAN mechanisms. This paper uses maritime diplomacy concept as its main analytical tools, consisting of three main diplomatic activities, which are cooperative maritime diplomacy, persuasive maritime diplomacy and coercive maritime diplomacy. This paper also uses qualitative methods with descriptive approach, and primary data derived from an interview with a diplomat of the Indonesian Ministry of Foreign Affairs and secondary datas were collected from various literatures and news. This article concludes that Indonesia’s diplomacy effort in support of AOIP is done under the cooperative maritime diplomacy framework by emphasizing the urgency to build an ASEAN-based Indo-Pacific cooperation concept amidst the emerging Indo-Pacific frameworks and visions pointed out by the great powers in the Indo-Pacific regions. This paper is conducted from 2014, where President Jokowi announce the maritime fulcrum foreign policy, to 2019 where the AOIP was established.